PEMANFAATAN RUANG MEDIA BUDIDAYA KERAMBA JARING APUNG MELALUI POLIKULTUR IKAN KERAPU (Serranidae), IKAN KUWE (Carangidae), DAN IKAN NAPOLEON (Cheilinus undulatus) - BOBY DANI DARMAWAN (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2009)
Commonly, the problem of using floating net cage is how to cultivate the commodity in limited space with high density to gain the maximum production. This study was therefore designed to answer that question. The habit of fishes which it live at the different space at water territorial such as demersal, pelagic, and benthic fishes was used in this research. The space usement for polyculture was done according to the fishes habit which its live at the different water territorial. Economical potent of the cultured fishes was also attended to get the profit from this business. According to the statement, the fishes used in this research was trevally (demersal), grouper (benthic), and napoleon wrasse (pelagic). The water space usement of floating net cage brought the positive things. The cultivated fishes growth with no problem such as the normally cultivation in a single space of floating net cage. The food is used optimally, shown with the food convertion ratio 5,13 : 1. The water space usement at this research not make some problem called competition in space usement and feeding either. Polyculture made the usement of floating net cage more efficient. The cultivation that normally used three places was minimized to became a single place. This manner also decreasing the time and the energy of the cultivator for feeding and nursering.